Garnet type solid electrolyte interface modification method

By pressing the stainless steel mesh on the surface of the garnet-type solid electrolyte to form a 3D pattern, the problems of poor interface contact of LLZO in lithium-ion batteries and the growth of lithium dendrites are solved, and better electrochemical performance and lower production costs are achieved.

CN119481252APending Publication Date: 2025-02-18HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411646045.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The application of garnet solid electrolyte (LLZO) in lithium-ion batteries is limited by the problems of poor interface contact and the growth of lithium dendrites. The existing interface modification methods are complex in technology, high in cost and limited in ability to suppress lithium dendrites.

Method used

By pressing the stainless steel mesh on the surface of the garnet-type solid electrolyte to form a 3D pattern, the contact area between the solid electrolyte and metal lithium is improved, the local current density is reduced, and the growth of lithium dendrites is delayed.

Benefits of technology

It achieves lower impedance, higher critical current density and more stable electrochemical performance, and the preparation process is simple and low cost, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481252A_ABST
    Figure CN119481252A_ABST
Patent Text Reader

Abstract

The invention discloses a garnet type solid electrolyte interface modification method which comprises the following steps: S1, respectively weighing LiCO3 powder, La2O3 powder, ZrO2 powder and Ta2O3 powder according to the stoichiometric ratio of elements in Li < 6.3 > La < 3 > Zr < 1.4 > Ta0. 6O12, and preparing Li < 6.3 > La < 3 > Zr < 1.4 > Ta0. 6O12 powder by adopting a wet ball milling process; s2, a three-layer structure of a stainless steel wire mesh-Li < 6.3 > La < 3 > Zr < 1.4 > Ta0. 6O12 powder-stainless steel wire mesh is laid in a grinding tool, the grinding tool is placed in a tablet press for tabletting, and a preliminarily-formed 3D-LLZTO electrolyte sheet is obtained; and S3, performing powder burying and sintering treatment on the preliminarily formed 3D-LLZTO electrolyte sheet, and then grinding and polishing to obtain the 3D-LLZTO electrolyte sheet. According to the invention, the interface contact is improved from the solid electrolyte matrix, the contact area of the solid electrolyte and the metal lithium is increased, the local current density is reduced, and the damage to the battery caused by the growth of lithium dendrites is delayed; after the prepared 3D-LLZTO solid electrolyte is assembled into a battery, the battery has lower impedance, higher CCD (Charge Coupled Device) and more stable electrochemical performance compared with the battery assembled by LLZT.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of garnet-type solid electrolytes, and in particular to a method for modifying the interface of garnet-type solid electrolytes. Background Art

[0002] In the current research in the field of batteries, lithium-ion batteries have excellent properties such as small size, light weight, high energy density, wide electrochemical window, and environmental friendliness, and are widely used. However, the electrolyte inside traditional liquid lithium-ion batteries is flammable and explosive, and its safety issues have attracted widespread attention. In contrast, solid electrolytes are stable in nature and can perfectly solve such safety issues. Solid electrolytes are mainly divided into oxide type and sulfide type. The oxide type includes garnet, perovskite, NASICON, LISICON and other structural types. Among them, garnet-type solid electrolytes (LLZO) have good prospects in the application of lithium-ion batteries.

[0003] LLZO has the advantages of high ionic conductivity, wide electrochemical window, excellent mechanical strength, good chemical stability and thermal stability and high safety. However, there are still some problems that limit its development:

[0004] (1) The solid-solid contact between LLZO and metallic lithium will lead to poor interface contact due to the influence of Li2CO3 on the surface of the solid electrolyte, resulting in high interface resistance and the growth of lithium dendrites. Therefore, it is necessary to modify the surface of LLZO.

[0005] (2) The current interface modification method mainly introduces an interface layer such as oxide, fluoride, nitride, etc. between the solid electrolyte and the electrolyte to improve the interface wettability. The strategy of introducing the interface layer as a buffer layer can effectively improve the contact of the solid-solid interface and reduce the growth of the interface impedance. However, the preparation process of the buffer layer is complicated, the cost is high, and the ability to inhibit lithium dendrites is limited, which cannot meet the requirements of market applications.

[0006] Another method of modifying the contact between the solid electrolyte and the electrode is to modify the metallic lithium negative electrode by doping. However, the method of doping the lithium negative electrode to form an alloy has a complicated preparation process, and the composite negative electrode is prone to volume expansion during the charge and discharge process and cannot ensure stability. Summary of the invention

[0007] To solve the above problems, the present invention provides a method for interface modification of garnet-type solid electrolyte, which can be applied to all-solid-state batteries and has excellent electrochemical properties, and has a simple preparation process, low cost, and can be industrially produced.

[0008] To achieve the above object, the present invention provides a method for modifying the interface of a garnet-type solid electrolyte, comprising the following steps:

[0009] S1. According to Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 LiCO3, La2O3, ZrO2 and Ta2O3 powders were weighed in the stoichiometric ratio of the elements and Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 powder;

[0010] S2. Lay stainless steel mesh inside the mold - Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 The three-layer structure of powder-stainless steel mesh is placed in a tablet press to make tablets. After the tablets are pressed, the stainless steel meshes on both sides of the electrolyte are peeled off. The stainless steel leaves a grid pattern on both sides of the electrolyte to obtain a preliminarily formed 3D-LLZTO electrolyte sheet.

[0011] S3. The initially formed 3D-LLZTO electrolyte sheet is subjected to powder embedding and sintering treatment, and then polished to obtain a 3D-LLZTO electrolyte sheet.

[0012] Preferably, the wet ball milling in step S1 comprises:

[0013] The weighed powders were mixed, ground using a high-speed ball mill with isopropanol as solvent to obtain a mixed slurry; the mixed slurry was dried to remove the organic solvent, and pre-sintered to obtain a white LLZTO block; the white LLZTO block was ball-milled to obtain a white slurry after drying to obtain Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 powder.

[0014] Preferably, the setting parameters of the high-speed ball mill are: rotation speed 200 rpm, ball milling time 17.5 h; to ensure uniform mixing of the raw materials, forward rotation for 1 h and then reverse rotation for 1 h.

[0015] Preferably, the stainless steel mesh needs to be pretreated before use, and the pretreatment includes:

[0016] Cutting: Cut the stainless steel mesh into round mesh pieces with a diameter of 12 mm;

[0017] Ultrasonic cleaning: the round mesh is ultrasonically cleaned in ethanol;

[0018] Drying: After ultrasonic cleaning, take out the round mesh and dry it.

[0019] Preferably, in step S2, the Li between the two layers of stainless steel mesh6.3 Ln3Z 1.4 Ta 0.6 O 12 The powder is filled evenly and tightly.

[0020] Preferably, in step S2, the pressure applied by the tablet press is 20 MPa.

[0021] Preferably, in step S3, the powder embedding sintering includes:

[0022] A layer of coarse Li particles with a particle size of about 40 mesh is covered on the surface of the initially formed 3D-LLZTO electrolyte sheet. 6.3 Ln3Z 1.4 Ta 0.6 O 12 The mother powder keeps the 3D-LLZTO electrolyte grooves clean, and then covers a layer of fine-grained Li with a particle size of 100 mesh. 6.3 Ln3Z 1.4 Ta 0.6 O 12 The mother powder is then sintered in a muffle furnace;

[0023] The sintering program was set as follows: the first stage, from room temperature to 100°C, with a heating rate of 3°C / min, and keeping warm for 2 h; the second stage, from 100°C to 450°C, with a heating rate of 3°C / min, and keeping warm for 2 h; the third stage, from 450°C to 1200°C, with a heating rate of 1°C / min, and keeping warm for 16 h; the fourth stage, from 1200°C to room temperature, with a cooling rate of 3°C / min.

[0024] The method for modifying the interface of a garnet-type solid electrolyte of the present invention has the following beneficial effects:

[0025] (1) The surface of the solid electrolyte is patterned (3D-LLZTO), and the interface contact is improved starting from the solid electrolyte matrix, thereby increasing the contact area between the solid electrolyte and metallic lithium, reducing the local current density, and delaying the growth of lithium dendrites that damage the battery. The prepared 3D-LLZTO solid electrolyte, after being assembled into a battery, has lower impedance, higher CCD, and more stable electrochemical performance than the battery assembled with LLZTO.

[0026] (2) Compared with the existing interface layer modification methods, due to the limitations of the methods themselves, such as strict preparation conditions, high requirements for substrate materials, low ionic conductivity of amorphous films, high preparation costs, etc., and the problem that traditional interface layers cannot avoid volume expansion, many interface layers have not been effectively used in all-solid-state batteries; the method of the present invention uses a stainless steel mesh to press a pattern on the surface of a solid electrolyte to make it 3D. Not only does the solid electrolyte produced have excellent electrochemical properties, but the preparation process is simple, the chemical composition is easy to control, the cost is low, and it is suitable for industrial production.

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The preparation flow chart of 3D-LLZTO electrolyte;

[0029] Figure 2 is the XRD pattern of 3D-LLZTO;

[0030] Figure 3 The electron microscope scanning images of 3D-LLZTO, where (a) is the real object of 3D-LLZTO; (b) is the cross section of 3D-LLZTO electrolyte;

[0031] Figure 4 EIS electrochemical performance characterization of Li / LLTZO / Li lithium symmetric battery and Li / 3D-LLTZO / Li lithium symmetric battery, wherein (a) is the EIS graph of Li / LLTZO / Li lithium symmetric battery at room temperature; (b) is the EIS graph of Li / 3D-LLTZO / Li lithium symmetric battery at room temperature;

[0032] Figure 5 The critical current density (CCD) test results of Li / LLTZO / Li lithium symmetric battery and Li / 3D-LLTZO / Li lithium symmetric battery, wherein (a) is the CCD graph of Li / LLTZO / Li lithium symmetric battery at 60°C, and (b) is the CCD graph of Li / 3D-LLTZO / Li lithium symmetric battery at 60°C;

[0033] Figure 6 These are the constant current cycle test results of Li / LLTZO / Li lithium symmetric battery and Li / 3D-LLTZO / Li lithium symmetric battery, where (a) is the constant current cycle diagram of Li / LLTZO / Li lithium symmetric battery at 60°C; (b) is the constant current cycle diagram of Li / 3D-LLTZO / Li lithium symmetric battery at 60°C. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages disclosed in the embodiments of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the embodiments of the present invention and are not intended to limit the embodiments of the present invention. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0035] Embodiment 1

[0036] A method for modifying the interface of a garnet-type solid electrolyte, the process of which is as follows Figure 1 As shown, the following steps are included:

[0037] Preparation of S1 and Ta-doped LLZTO master powder

[0038] According to Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 According to the stoichiometric ratio, LiCO3, La2O3, ZrO2 and Ta2O3 powders are weighed on an electronic balance, wherein LiCO3 needs to be weighed 10% more to make up for lithium loss, and La2O3 powder needs to be pre-calcined in a muffle furnace to remove moisture. In this embodiment, 54.95g of LiCO3, 29.38g of La2O3, 19.60g of ZrO2 and 14.90g of Ta2O3 are weighed to obtain a total of 100g of LLZTO master powder.

[0039] After the powders were mixed, they were ground using a high-speed ball mill using isopropanol as a solvent. The setting parameters of the high-speed ball mill were: speed 200 rpm, ball milling time 17.5 h; to ensure uniform mixing of the raw materials, forward rotation for 1 h and reverse rotation for 1 h.

[0040] The mixed slurry obtained by the first ball milling was dried to obtain a white mixed powder. The white mixed powder was sintered in a muffle furnace at 950°C for 6 hours to obtain a white LLZTO block. The white LLZTO block was ball milled for the second time, and the setting parameters were the same as the first ball milling. The white slurry obtained by the second ball milling was dried to obtain Ta-doped LLZTO master powder.

[0041] S2. Abrasive tool pretreatment

[0042] Select stainless steel mesh as the abrasive material and cut it into round mesh pieces with a diameter of 12 mm. Ultrasonic clean the cut stainless steel mesh in ethanol to remove stains and impurities on the surface. After cleaning, take out the stainless steel mesh and dry it to ensure that the surface is dry and free of residue.

[0043] S3, tableting

[0044] Place a pretreated stainless steel mesh in the tablet press mold, and evenly spread the Ta-doped LLZTO mother powder on the stainless steel mesh to ensure that the mother powder is evenly and tightly filled. Place another stainless steel mesh on top of the mother powder to form a three-layer structure of "stainless steel mesh-mother powder-stainless steel mesh". Place the tablet press mold in the tablet press and apply a pressure of 20MPa to form the mother powder between the stainless steel meshes. Remove the stainless steel mesh in the mold to obtain a preliminarily formed 3D-LLZTO electrolyte sheet.

[0045] S4, powder sintering

[0046] A layer of 40-mesh coarse-grained master powder was covered on the surface of the 3D-LLZTO electrolyte sheet to keep the surface grooves of the 3D-LLZTO electrolyte clean, and then a layer of fine-grained master powder screened by a 100-mesh sieve was used to cover it.

[0047] The treated electrolyte sheet was placed in a muffle furnace for sintering. The sintering program was set as follows: the first stage, room temperature (25°C) to 100°C, heating rate 3°C / min, heat preservation for 2h; the second stage, 100°C to 450°C, heating rate 3°C / min, heat preservation for 2h; the third stage, 450°C to 1200°C, heating rate 1°C / min, heat preservation for 16h; the fourth stage, 1200°C to room temperature, cooling rate 3°C / min.

[0048] S5. Grinding and polishing

[0049] After sintering, the 3D-LLZTO electrolyte sheet needs to be polished to reach a diameter of 10 mm and a thickness of 1 mm. During the polishing process, care should be taken to maintain the shape and integrity of the electrolyte sheet to avoid cracks or breakage.

[0050] Embodiment 2

[0051] A method for preparing a garnet-type solid electrolyte, which is different from Example 1 in that:

[0052] (1) Tableting: directly put the Ta-doped LLZTO mother powder into a mold, place the mold in a tablet press, apply a pressure of 20 MPa, and obtain LLZTO electrolyte sheets.

[0053] (2) Buried powder sintering: A layer of Ta-doped LLZTO mother powder is covered on the surface of the LLZTO electrolyte sheet and placed in a muffle furnace for sintering.

[0054] The sintering program was set as follows: the first stage, room temperature (25°C) to 100°C, heating rate of 3°C / min, keeping warm for 2h; the second stage, 100°C to 450°C, heating rate of 3°C / min, keeping warm for 2h; the third stage, 450°C to 1200°C, heating rate of 1°C / min, keeping warm for 16h; the fourth stage, 1200°C to room temperature, cooling rate of 3°C / min.

[0055] The sintered LLZTO electrolyte sheet was ground and polished to finally prepare a non-3D LLZTO electrolyte sheet.

[0056] Experimental Testing

[0057] (I) XRD test collects the corresponding characteristic peaks and compares them with the standard cubic phase and tetragonal phase peaks in the database to determine whether the desired product phase is generated. At the same time, the appearance of impurity peaks can also be observed. The D2-PHASER model instrument is used, with a Cu target radiation source at a voltage of 40KV and a scanning range of 10° to 80°.

[0058] The results are as follows Figure 2 As shown, it is the XRD spectrum of 3D-LLZTO. The spectrum peaks are consistent with the standard spectrum and have a pure cubic phase structure.

[0059] (ii) The Phenom Prox scanning electron microscope was used to perform microscopic morphology analysis on the doped solid electrolyte samples and observe the 3D surface and cross-section of the patterned solid electrolyte (3D-LLZTO).

[0060] The results are as follows Figure 3 As shown, (a) is the actual 3D-LLZTO, whose surface presents a mesh structure; (b) is the cross-section of the 3D-LLZTO electrolyte, which presents arc grooves.

[0061] (III) The non-3D-electrolyte LLZTO in Example 2 and the 3D-LLZTO in Example 1 were assembled into lithium symmetric batteries, and the electrochemical performance was characterized by EIS.

[0062] like Figure 4 As shown, (a) is the EIS graph of the Li / LLTZO / Li lithium symmetric battery assembled by the non-3D LLZTO in Example 2 at room temperature; (b) is the EIS graph of the Li / 3D-LLTZO / Li lithium symmetric battery assembled by the 3D-LLZTO in Example 1 at room temperature. It can be seen that the matrix impedance and interface impedance of the LLZTO modified after surface 3D are both reduced. This is because the 3D groove shortens the actual distance between the positive and negative electrodes while the thickness of the electrolyte remains unchanged, so that the matrix impedance is smaller than that of the battery assembled by LLZTO of normal specifications; the interface contact between 3D-LLZTO and the lithium electrode is improved, so the interface impedance is reduced.

[0063] (IV) Critical current density (CCD) test

[0064] Critical current density (CCD) refers to the maximum current density that a battery can withstand during the charge and discharge process. Once this density is exceeded, the stability of the battery is destroyed, the performance decreases rapidly, and eventually the battery is damaged. Therefore, the critical current density (CCD) is used to analyze the ability of lithium batteries to resist the growth of lithium dendrites.

[0065] The assembled battery was taken out after standing in the glove box for 12 hours, and the battery was clamped in the order of positive and negative poles. The solid-state battery was subjected to an electrochemical stripping / plating test for 0.5 hours at a constant temperature of 60°C using a Neware electrochemical testing system (NEWARE CT-4000) with gradually increasing current to evaluate the critical current density (CCD) of the battery.

[0066] The results are as follows Figure 5 As shown, (a) is the CCD image of the Li / LLTZO / Li lithium symmetric battery assembled with LLZTO without 3D at 60°C in Example 2, and (b) is the CCD image of the Li / 3D-LLTZO / Li lithium symmetric battery assembled with 3D-LLZTO in Example 1 at 60°C. Among them, the surface 3Dization makes the CCD of the lithium symmetric battery from 0.3 mA·cm -2 Increased to 1.02 mA cm -2 This indicates that after the Ta-doped LLTZO surface is 3D-ized, the interface problem between the electrode and the solid electrolyte is improved, and the battery's ability to resist lithium dendrites becomes stronger.

[0067] (V) Constant current cycle test

[0068] Constant current cycle test is one of the core methods of battery performance evaluation. During the test process, a constant current is applied to the battery, and the dynamic relationship between time and voltage is accurately recorded. Constant current cycle test can evaluate the cycle stability and life of the battery.

[0069] The assembled battery was placed in the glove box for 12 h and then taken out. The battery was clamped in the order of positive and negative electrodes. The Neware electrochemical test system (NEWARE CT-4000) was used to test 0.15 mA cm at a constant temperature of 60 °C with a fixed plating / stripping interval of 0.5 h. -2 Long cycle performance of the battery at high current density.

[0070] The results are as follows Figure 6 As shown, (a) is a constant current cycle diagram of the Li / LLTZO / Li lithium symmetric battery assembled with the non-3D LLZTO in Example 2 at 60°C; (b) is a constant current cycle diagram of the Li / 3D-LLTZO / Li lithium symmetric battery assembled with the 3D 3D-LLZTO in Example 1 at 60°C.

[0071] It can be seen that the Li / LLTZO / Li lithium symmetric battery short-circuited after 60 h, and the Li / 3D-LLTZO / Li lithium symmetric battery short-circuited at 0.15 mA cm -2 It can remain stable after 1200 h of stably cycling at a current density of , showing excellent cycle stability.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for modifying the interface of a garnet-type solid electrolyte, characterized in that: The steps include: S1. According to Li 6.3 LqCy 1.4 Ta 0.6 O 12 LiCO3, La2O3, ZrO2 and Ta2O3 powders were weighed in the stoichiometric ratio of the elements and Li 6.3 LqCy 1.4 Ta 0.6 O 12 Mother powder; S2. Lay stainless steel mesh inside the mold - Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 The three-layer structure of mother powder and stainless steel mesh is placed in a tablet press to make tablets. After the tablet is pressed, the stainless steel mesh is peeled off to obtain a preliminarily formed 3D-LLZTO electrolyte sheet. S3. The initially formed 3D-LLZTO electrolyte sheet is subjected to powder embedding and sintering treatment, and then polished to obtain a 3D-LLZTO electrolyte sheet.

2. The method for modifying the interface of a garnet-type solid electrolyte according to claim 1, characterized in that: The wet ball milling in step S1 includes: The weighed powders are mixed, ground using isopropyl alcohol as a solvent using a high-speed ball mill to obtain a mixed slurry; The mixed slurry is sintered to remove the organic solvent to obtain a white LLZTO block; The white LLZTO block is ball-milled, and the obtained white slurry is dried to obtain Li 6.3 Ln3Z 1.4 Ta 0.6 O 12 Mother powder.

3. The method for modifying the interface of a garnet-type solid electrolyte according to claim 2, characterized in that: The setting parameters of the high-speed ball mill are: rotation speed 200 rpm, ball milling time 17.5 h; to ensure uniform mixing of the raw materials, forward rotation for 1 h and then reverse rotation for 1 h.

4. The method for modifying the interface of a garnet-type solid electrolyte according to claim 1, characterized in that: Stainless steel mesh needs to be pretreated before use, the pretreatment includes: Cutting: Cut the stainless steel mesh into round mesh pieces with a diameter of 12 mm; Ultrasonic cleaning: the round mesh is ultrasonically cleaned in ethanol; Drying: After ultrasonic cleaning, take out the round mesh and dry it.

5. The method for interface modification of a garnet-type solid electrolyte according to claim 1, characterized in that: In step S2, the Li between the two layers of stainless steel mesh 6.3 Ln3Z 1.4 Ta 0.6 O 12 The mother powder is filled evenly and tightly.

6. The method for modifying the interface of a garnet-type solid electrolyte according to claim 1, characterized in that: In step S2, the pressure applied by the tablet press is 20 MPa.

7. The method for modifying the interface of a garnet-type solid electrolyte according to claim 1, characterized in that: In step S3, powder embedding and sintering includes: A layer of coarse-grained Li with a particle size of 40 mesh is covered on the surface of the initially formed 3D-LLZTO electrolyte sheet. 6.3 LqCy 1.4 Ta 0.6 O 12 Mother powder, and then covered with a layer of fine particles of Li with a particle size of 100 mesh 6.3 LqCy 1.4 Ta 0.6 O 12 The mother powder is then sintered in a muffle furnace; The sintering program was set as follows: the first stage, from room temperature to 100°C, with a heating rate of 3°C / min, and keeping warm for 2 h; the second stage, from 100°C to 450°C, with a heating rate of 3°C / min, and keeping warm for 2 h; the third stage, from 450°C to 1200°C, with a heating rate of 1°C / min, and keeping warm for 16 h; the fourth stage, from 1200°C to room temperature, with a cooling rate of 3°C / min.

8. The method for modifying the interface of a garnet-type solid electrolyte according to claim 1, characterized in that: In step S1, 10% more LiCO3 powder is weighed to make up for lithium loss, and La2O3 powder is pre-calcined in a muffle furnace to remove moisture.